1992
DOI: 10.1099/00221287-138-7-1317
|View full text |Cite
|
Sign up to set email alerts
|

Lack of homology between two haloacetate dehalogenase genes encoded on a plasmid from Moraxella sp. strain B

Abstract: Two genes encoding haloacetate dehalogenases, H-1 and H-2, are closely linked on a plasmid from Moraxellu sp. strain B. H-1 predominantly acts on fluoroacetate, but H-2 does not. To elucidate the molecular relationship between the two enzymes, we compared their structural genes. Two restriction fragments of the plasmid DNA were subcloned on M13 phages and their nucleotide sequences were determined. The sequence of each fragment contained an open reading frame that was identified as the structural gene for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 25 publications
1
74
0
Order By: Relevance
“…The microbial dienelactone hydrolase hydrolyzes dienelactone to maleylacetate and has esterase activity toward other substrates (Pathak et al, 1991;Beveridge and Ollis, 1995). Haloacetate dehalogenase acts specifically on halogenated acetates to yield glycolate as a carbon source in microorganisms (Kawasaki et al, 1992). Epoxide hydrolase catalyzes the conversion of epoxides to diols.…”
Section: Discussionmentioning
confidence: 99%
“…The microbial dienelactone hydrolase hydrolyzes dienelactone to maleylacetate and has esterase activity toward other substrates (Pathak et al, 1991;Beveridge and Ollis, 1995). Haloacetate dehalogenase acts specifically on halogenated acetates to yield glycolate as a carbon source in microorganisms (Kawasaki et al, 1992). Epoxide hydrolase catalyzes the conversion of epoxides to diols.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that there is no homology between dehH1 and dehH2. 4 ) H-2 has less activity against 2-chloropropionate than H-I09 has, but other catalytic properties are similar between H-2 and H-I09. The length of dehH2 is 675bp that is identical with that of dehH109, and dehH2 and dehH109 had 58% similarity in the nucleotide sequence and 51 % similarity in the amino acid sequence.…”
Section: Nucleotide Sequence Of the Gene Dehh109mentioning
confidence: 99%
“…Moraxella B (DehH1, Genbank/EMBL Accession Number D90422; Kawasaki et al, 1992), tetrachlorocyclohexadiene dehalogenase from Sphingomonas paucimobilis (LinB, D14594; Nagata et al, 1993), and 1-chloroalkane halidohydrolase from Rhodococcus rhodochrous NCIMB13064 (DhaA, L49435; Kulakova et al, 1997) showed that they have considerable homology with DhlA (M26950), suggesting FIGURE 2: Sequence alignment of haloalkane dehalogenase from Xanthobacter autotrophicus GJ10 (DhlA; Janssen et al, 1989), haloacid dehalogenase from Moraxella B (DehH1; Kawasaki et al, 1992), tetrachlorocyclohexadiene dehalogenase from Sphingomonas paucimobilis (LinB; Nagata et al, 1993), and 1-chloroalkane halidohydrolase from Rhodococcus rhodochrous NCIMB13064 (DhaA; Kulakova et al, 1997). The sequence comparison was carried out using the program DNASTAR (DNASTAR Inc., Madison, WI).…”
Section: Sequence Alignment Of R/ -Hydrolase Fold Dehalogenases Sequmentioning
confidence: 99%